2012
DOI: 10.1016/j.amjsurg.2011.07.023
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ambulatory perioperative times in hospitals and freestanding centers

Abstract: BACKGROUND The volume of surgical procedures performed in ambulatory surgical centers has increased rapidly. METHODS Ambulatory surgical visits of Medicare beneficiaries were compared for hospital-based and freestanding ambulatory surgical centers (ASCs). The main outcomes were time in surgery, time in operating room, time in postoperative care, and total perioperative time. RESULTS The mean total perioperative time for all procedures examined was 39% shorter in freestanding ASCs then in hospital-based ASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Finally, the hospital setting and environment has a large influence on levels of efficiency of first starts and turnover, for example, freestanding ambulatory surgery centres (ASC) being much more efficient than those ASCs that are part of a larger hospital, with additional variations with hospitals of different sizes and different patient populations, and/or the addition of trainees in the mix as noted . While we have a challenging environment based on our patient population, multiple trainees on both the surgery and anaesthesiology teams; implementation of a pre‐operative complete checklist in addition to a dedicated OR facilitator, all of which need to be taken into account, we were able to make a substantial improvement in our first start on time starts.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the hospital setting and environment has a large influence on levels of efficiency of first starts and turnover, for example, freestanding ambulatory surgery centres (ASC) being much more efficient than those ASCs that are part of a larger hospital, with additional variations with hospitals of different sizes and different patient populations, and/or the addition of trainees in the mix as noted . While we have a challenging environment based on our patient population, multiple trainees on both the surgery and anaesthesiology teams; implementation of a pre‐operative complete checklist in addition to a dedicated OR facilitator, all of which need to be taken into account, we were able to make a substantial improvement in our first start on time starts.…”
Section: Discussionmentioning
confidence: 99%
“…Shorter perioperative times were also reported in a retrospective study by Hair et al, which found significantly shorter surgery times, operating room times and postoperative times at freestanding ASCs compared to hospital-based outpatient surgery centers across surgical specialties. 23 These differences support the theory that ASCs are more efficient in their processes.…”
Section: Discussionmentioning
confidence: 53%
“…The first is the 2006 National Survey of Ambulatory Surgery (NSAS), which records OR times and surgical times, but not anesthesia times. This data source from the National Center for Health Statistics covers a wide range of procedures that are performed in hospital ambulatory settings or freestanding ambulatory surgery centers, but not the inpatient setting (Hair, Hussey, and Wynn ). It is not feasible to use the NSAS data to estimate CPT‐level procedure times as NSAS records procedures according to an alternative coding system, the ICD‐9 system.…”
Section: Methodsmentioning
confidence: 99%